A Selective Copper Based Oxygen Reduction Catalyst for the Electrochemical Synthesis of H2O2 at Neutral pH. Issue 3 (2nd February 2022) - van Dijk, Bas; Kinders, Rick; Ferber, Thimo H.; Hofmann, Jan P.; Hetterscheid, Dennis G. H.
Abstract: H2 O2 is a bulk chemical used as "green" alternative in a variety of applications, but has an energy and waste intensive production method. The electrochemical O2 reduction to H2 O2 is viable alternative with examples of the direct production of up to 20% H2 O2 solutions. In that respect, we found that the dinuclear complex Cu2 (btmpa) (6, 6'‐bis[[bis(2‐pyridylmethyl)amino]methyl]‐2, 2'‐bipyridine) reduces O2 to H2 O2 with a selectivity up to 90 % according to single linear sweep rotating ring disk electrode measurements. Microbalance experiments showed that complex reduction leads to surface adsorption thereby increasing the catalytic current. More importantly, we kept a high Faradaic efficiency for H2 O2 between 60 and 70 % over the course of 2 h of amperometry by introducing high potential intervals to strip deposited copper ( dep Cu). This is the first example of extensive studies into the long term electrochemical O2 to H2 O2 reduction by a molecular complex which allowed to retain the high intrinsic selectivity of Cu2 (btmpa) towards H2 O2 production leading to relevant levels of H2 O2 . Abstract : Optimised catalytic activity : Electrochemical H2 O2 production is a promising sustainable alternative to the anthraquinone method. In that perspective, we have studied the dinuclear copper complex Cu2 (btmpa) that has a high intrinsic H2 O2 selectivity. By extensive, long term studies, we found that complex accumulation on the electrode increases the catalytic activity and that high potential intervals strip away deposited copper. Through this procedure we were able to reach a 60 to 70 % Faradaic efficiency during long term amperometry experiments.